Influences on the access to and use of formal community care by people with dementia and their informal caregivers: a scoping review - Anja Bieber; Natalie Nguyen; Gabriele Meyer; Astrid Stephan (BMC, 2019)
Abstract Background The literature describes the obstacles to sufficient care faced by people with dementia and their informal caregivers. Although factors influencing access and utilisation are frequently studied, the body of knowledge lacks an overview of aspects related to influence. The frequently used Behavioural Model of Health Care Use (BM) could be used to structure and explain these aspects. An adaptation of the BM emphasises psychosocial influences and appears to enrich the understanding of the use of long-term care for dementia. Methods We conducted a scoping review with the aim of providing an overview of the aspects influencing the access to and utilisation of formal community care in dementia. Our search covered the PubMed, CINAHL, Social Science Citation Index and PsychInfo databases, as well as grey literature. Two researchers assessed the full texts for eligibility. A data extraction form was developed and tested. We analysed the main topics investigated by the studies and mapped and described the investigated psychosocial aspects according to the BM after narratively summarising the findings. We used the Mixed Method Appraisal Tool (MMAT) to critically appraise the included studies. Results A total of 94 studies were included: n = 55 with quantitative designs, 35 with qualitative designs and four with mixed methods. The studies investigated different services, mainly focusing on health care services. One third of the studies provided information regarding the severity of dementia. The most frequently investigated main topics were ethnicity and attitudes towards services. Psychosocial aspects were frequently investigated, although few studies considered the perspectives of people with dementia. Approximately half of the studies reported a theoretical framework. The adapted BM facilitated the structuring and description of psychosocial aspects. However, this instrument did not address topics beyond the scope of psychosocial aspects, such as sociodemographic characteristics. Conclusions The access to and utilisation of formal community care for dementia can only be partly explained by individual influencing aspects. Therefore, a theoretical framework would likely help to describe this complex subject. Our findings indicate that the psychosocial categories of the adapted BM enriched the original BM, and that people with dementia should more often be included in healthcare service research to ensure a better understanding of the barriers to accessing formal community care.